Praktik Gala Umong dan Dampaknya Terhadap Perekonomian Masyarakat Perspektif Hukum Ekonomi Syariah - Makraja, Fahmi; Putri, Raihan (Al Ahkam, 2024)
The practice of gala umong carried out in the community is an alternative option in solving the economic problems they face. The fundamental reason for implementing gala umong among the community is because the process of carrying out the contract is very short and does not require a long time. Gala umong, which means pawning rice fields, is a practice often heard in Acehnese society. Gala umong is almost practiced throughout the entire Aceh region, including Gampong Pusu Ingin Jaya, Manggeng District, Southwest Aceh Regency. The practice of gala umong is carried out as an alternative in order to solve the economic problems they face. Gala gatherings are held between neighbors or close relatives. This research explores the practice of gala umong in the community using a descriptive qualitative approach. The results of this research show that the gala umong held in Pusu Ingin Jaya Village had a significant impact on improving the community's economic sector. The positive impact is that rice field owners can earn money in the near future to finance their daily needs, start a business, and pay for educational costs. The negative impact felt by rahin and murtahin is increasing social inequality and reducing farmers' livelihoods due to their rice fields being used as collate The negative impact felt by rahin and murtahin is the increasing social inequality and the reduction of farmers' livelihoods due to their rice fields being used as collateral. When viewed from a sharia economic perspective, the implementation of the gala umong that occurred in Pusu Ingin Jaya Village was not in accordance with the binding elements in it. There are some pledge requirements that have not been fulfilled, namely there is no written evidence and no witnesses.